Formação docente frente às tecnologias digitais da informação e da comunicação: o caso dos cursos de Licenciatura da Universidade Federal de Sergipe – Campus São Cristóvão - Santa Rosa, Josefa Risomar Oliveira (2019)
This dissertation is linked to the research line ‘Education and Communication’ and has as study object the undergraduate courses of Federal University of Sergipe (UFS), São Cristóvão campus, with the purpose to understand how curricular components for the Digital Information and Communication Technologies (DICT) are articulated, in face of the current demands, in the initial teachers’ education formation. In order to achieve the goal on the screen, the following specific objectives were defined: to characterize the digital culture by identifying the digital technology aspects that express new cognitive and socio-emotional demands on people in the contemporary world; to analyze the curricular matrices of undergraduate courses of UFS São Cristóvão that are articulated to the DICT; to discuss what is the DICT place in the initial teachers’ education, based on the analysis of the documents identified in the previous specific objective, and whether they are compatible with an education able of developing digital wisdom in the licensed. In this sense, it is necessary that the education professional has a formation that enables him to face the challenges imposed in his teaching practice in a conscious way of his role as a critical and reflexive mediator about technologies use in education area, avoiding pedagogical ‘fashions’ temptation. Data were collected through documentary research of the subject programs and menus of the presential undergraduate courses of UFS São Cristóvão Campus. It is, therefore, a qualitative research, developed through a bibliographic review from exploratory type and from documentary analysis. The chosen means to locate and obtain the matrices, offer occurrence of the subjects directed to the DICT in the 23 institutions face-to-face licensed degrees courses. The results point to the lack of curricular components in six (06) courses, and from the seventeen (17) courses that present subjects articulated with the DICT, nine (09) are of optative nature. The subject, as it is optional, gives the impression of lack of priority in the whole formation, while it should be seen as an instrument to be used to keep the course proposal updated. It is concluded that the DICT of undergraduate courses of UFS are insufficient for teacher’s formation, which will impact the possibility of future graduates to apply them coherently in their pedagogical practices, given that society has evolved and teaching need to keep up with this evolution.